(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Miracle berry (Synsepalum dulcificum) is a plant with unique taste-altering properties, which converts the sour taste of foods into sweetness. Therefore, it is highly interesting to incorporate it into kombucha, a well-known fermented product. This study aims to evaluate the effect of microwave radiation (MR) on the physicochemical and microbial properties of miracle berry kombucha tea (MBK) treated with MR. In this study, 75% miracle berry and 25% black tea kombucha were subjected to MR at varying times (5s and 10s). The total soluble solid (TSS) and pH, color, colony count of acetic acid bacteria (AAB) and lactic acid bacteria (LAB) were determined. Results showed that the pH and TSS values decreased over time, with microwave-treated samples exhibiting higher values than the control. The microwave-treated MBK at 5s significantly (p<0.05) promoted the growth of LAB (0.00 to 5.70 CFU/mL) from day 0 to 7 but inhibited the growth of AAB. In conclusion, the observed fermentation throughout 7 days of storage potentially shortened the fermentation period, and MBK under 5s treatment potentially enhanced the LAB growth. This study can provide fresh perspectives on the effects of MR on kombucha quality and properties.